A mineralogical investigation of the Late Permian Doba gabbro, southern Chad: Constraints on the parental magma conditions and composition. (February 2016) - Shellnutt, J. Gregory; Lee, Tung-Yi; Yang, Chih-Cheng; Hu, Shin-Tai; Wu, Jong-Chang; Iizuka, Yoshiyuki
Abstract: The late Permian Doba (257 ± 1 Ma) gabbro was discovered at the base of an exploration well through the Cretaceous Doba Basin of Southern Chad. The gabbro is at least 250 m thick, has cumulus mineral textures and consists of plagioclase, clinopyroxene, orthopyroxene, Fe–Ti oxide, apatite and quartz. The composition of the silicate minerals (i.e. plagioclase, pyroxenes) from the lowest part of the intrusion tend to be more primitive (i.e. An59, Wo40-44 En33-47 Fs12-25 ) than the upper part (i.e. An41, Wo39-43 En30-44 Fs14-29 ) suggesting the magmatic system differentiated internally by crystal fractionation and crystal redistribution. Based on the chemistry of the pyroxenes, the parental magma was compositionally similar to a Ti-rich, within-plate continental tholeiite that had a bulk Mg# of ∼44. The relative oxidation state of the magma was initially moderately reducing (i.e. ΔFMQ-0.3) and then became more reducing after a period of fractionation (i.e. ΔFMQ-1.2). The estimated initial magma temperature was at least 1100 °C. The within-plate composition suggests there was rifting-related magmatism near the boundary of the Saharan Metacraton that could be related to edge-driven mantle convection. Graphical abstract: Highlights: The Doba gabbro is a mafic cumulate textured intrusion from southern Chad. The parental magma was similar to a Ti-rich within-plate continental tholeiite. The Doba intrusion was a magma chamber and likely lost a residual silicic liquid. Eruption of flood basalts likely occurred in southern Chad during the late Permian.